La cooperación bilateral Ecuador – China. Período 2007 – 2013 - Romo Arellano, Luis Hernando (2014)
The analysis of the Ecuador - China bilateral cooperation is an approach to the framework for action that both countries have been developing since three decades ago, when they established diplomatic relations. However, since the advent to power of President Rafael Correa, different missions deployed to China, have resulted in the signing of agreements on topics of interest to both States. Governmental management in Ecuador has sought to arrange a wide range of proposals for compliance with the principles of the 2008 Constitution and the objectives of the National Plan for good living with China 2009-2013 and 2013-2017. The national government instruments that articulate public policies of international relations of the Ecuadorian State. China on the basis of the principles of harmonious development in the bilateral relationship with Ecuador, considered that proposals for Ecuador are part of the political vision of the strategies of the paradigm shift of a State socialism planned towards a transformation process of market socialism, with emphasis on a policy of South-South cooperation, as strategic partners in trade relations, and consensus of an international agenda on issues of interest for the States and the world.